Investigating the validity of the Australian EarlyDevelopment Index - Silburn, S; Lawrence, D; Brinkman, S (My University, 2007)
The Australian Early Development Instrument (AEDI) is an Australian adaptation of the Canadian Early Development Instrument. It is a child development and school readiness instrument, administered by teachers, that communities can use to monitor their children's development. To examine its construct and concurrent validity, this study compares the AEDI against results from the Longitudinal Study of Australian Children (LSAC), which is a longitudinal study involving parent, teacher, and interviewer assessments of infants and preschool children. Using a sub-sample of children from Queensland, Victoria, and Western Australia, the authors compared measures for social competence, language and cognitive development, emotional maturity, and health and wellbeing. Though there were moderate to strong correlations with LSAC measures on many domains, findings for concurrent validity were inconclusive, and the authors await future waves of LSAC data to provide further data to measure against.
Early Education and Development
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology